Sistem Manajemen Keselamatan, Kesehatan Kerja, Dan Produktivitas Kerja Karyawan Di Pt Matahari Putra Prima, Tangerang - Dawud Dawud; Aminudin Aminudin (Indonesian Journal of Economics Application (IJEA), 2020)
The objectives of this study are: (1) to analyze the effect of occupational safety and health management systems (SMK3) on employee productivity at PT Matahari Putra Prima Tbk in Karawaci, Tangerang Regency. Associative descriptive research methods and surveys with quantitative approaches used in this research. The sample studied was 78 employees. Analysis results: firstly, occupational safety and health management system (SMK3), there is a positive relationship with employee productivity at PT Matahari Putra Prima Tbk. in Karawaci, Tangerang Regency, in other words, the better the Occupational Safety and Health Management System (SMK3), the better the Employee Productivity. Secondly, the results of the Determination Coefficient analysis show that the Occupational Safety and Health Management System (SMK3) affects Employee Productivity at PT Matahari Putra Prima Tbk. in Karawaci, Tangerang Regency was 58.0% while the remaining 42.0% was influenced by other factors which were not further analyzed by researchers.